Vibrational Properties of the Phosphate Group Investigated by Molecular Dynamics and Density Functional Theory - Andrushchenko, Valery; Benda, Ladislav; Páv, Ondřej; Dračínský, Martin; Bouř, Petr (The journal of physical chemistry. B, 2015)
The phosphate group (PO2(-)) is an important building block occurring in many components of living matter including nucleic acids. It provides distinct features in vibrational spectra and is useful as a local probe of NA conformation and interactions with the environment. For this purpose, it is desirable to explore in detail various factors influencing spectral shapes of characteristic phosphate vibrations. In the present study, effects of the solvent and conformational averaging are analyzed for simple model molecules, dimethylphosphate, ethylmethylphosphate, and ethylmethylthiophosphate. Infrared absorption (IR) and Raman spectra were measured and calculated using a combination of molecular dynamics (MD) and density functional theory (DFT). To fully understand the link between the structure and the spectra, the solvent has to be explicitly included in the computational modeling. The results indicate that vibrational properties of the phosphate moiety are very sensitive to its conformation and interactions with the aqueous environment indeed. Polarizable continuum solvent models without explicit water molecules provided significantly worse agreement with the experiment. The combined MD/DFT approach captures well spectral characteristics for the model systems and constitutes the most reliable basis for exploration of phosphate vibrational properties in biomolecular structural studies.
Keywords: molekulární konformace; Hydrogen Bonding; fosfáty; vodíková vazba; simulace molekulární dynamiky; termodynamika; Molecular Conformation; Quantum Theory; Thermodynamics; Molecular Dynamics Simulation; Vibration; kvantová teorie; Phosphates; vibrace